2022
DOI: 10.1007/s10479-022-04930-x
|View full text |Cite
|
Sign up to set email alerts
|

Robust possibilistic programming to design a closed-loop blood supply chain network considering service-level maximization and lateral resupply

Abstract: Reconfiguring the structure of the supply chain network is one of the most strategic and vital decisions in designing a supply chain network. In this study, a Closed-Loop Blood Supply Chain Network (CLBSCN) considering blood group compatibility, ABO-Rh(D), and blood product shelf life has been studied to determine the best strategic and tactical decisions simultaneously considering lateral resupply/transshipment and service-level maximization. Several vital parameters, including supply and demand, are consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…They also incorporated socio-economic factors and pandemic impacts into their Blood Supply Chain (BSC) model. In their paper, Momenitabar et al 35 proposed a fuzzy multi-objective Mixed-Integer Nonlinear Programming (MINLP) model with the goal of minimizing total network costs and maximizing service levels in hospitals. The case study demonstrated significant cost savings and improved service levels by incorporating lateral resupply strategies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They also incorporated socio-economic factors and pandemic impacts into their Blood Supply Chain (BSC) model. In their paper, Momenitabar et al 35 proposed a fuzzy multi-objective Mixed-Integer Nonlinear Programming (MINLP) model with the goal of minimizing total network costs and maximizing service levels in hospitals. The case study demonstrated significant cost savings and improved service levels by incorporating lateral resupply strategies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This section proposes the charging location model on a fully electric public transit network. The proposed network comprises nodes representing the bus stops that are candidate places for locating fast and ES chargers, and links representations of the connections of road sections between two bus stops in the network (21)(22)(23)(24). The fast chargers with/without ES technology are shown in Figure 1.…”
Section: Mathematical Formulationmentioning
confidence: 99%
“…The authors also consider pre-and post-disaster modes, investigate flow between centres, and employ a robust optimization approach for solving the proposed model, demonstrating its effective performance. Momenitabar et al (2022) focus on the reconfiguration of a closed-loop blood supply chain network considering blood group compatibility and blood product shelf-life. A fuzzy multi-objective mixed-integer non-linear programming model is proposed to minimize network costs and maximize the minimum service level to patients.…”
Section: Literature Reviewmentioning
confidence: 99%